Effect of feeding napier grass, lucerne and sweet potato vines as sole diets to dairy heifers on nutrient intake, weight gain and rumen degradation - Kariuki, J.N.; Gachuiri, C.K.; Gitau, G.K.; Tamminga, S.; Bruchem, J. van; Muia, J.M.K.; Irungu, K.R.G. (Elsevier, 1998)
Two experiments were conducted to assess the nutrient intake, weight gain (ADG) and rumen degradation of napier grass (NG), lucerne (L) and sweet potato vines (SPV) fed to growing dairy heifers. In the first experiment, 33 Friesian heifers were randomly allocated to the three treatments namely; napier grass, lucerne and sweet potato vines which were fed for 104 days. In the second experiment, degradability of the three diets was estimated using nylon bags incubated in two rumen fistulated steers. The mean chemical composition of the forages were: dry matter (DM) 155, 807 and 123 g kg-1; organic matter (OM), 796, 854 and 852 g kg-1 DM; crude protein (CP), 118, 167 and 135 g kg-1 DM and neutral detergent fibre (NDG), 587, 408 and 506 g kg-1 DM for NG, L and SPV, respectively. The mean daily DM intake was 5.0, 5.5, and 4.2 kg while the CP intake was 0.59, 0.96 and 0.57 g for diets NG, L and SPV (P<0.05). The ADG from NG, L and SPV were 0.50, 0.67 and 0.50 kg day-1, respectively. The SPV diet showed higher effective degradability than L and NG (P<0.05), while the latter two forages were not significantly different (P>0.05). It was concluded from the study that NG, L and SPV contained nutrient levels that would sustain acceptable growth in heifers.